Investigation of Pre-Service Teachers’ Global Literacy Levels - Bulut, Bırol; Öksüzoğlu, Muhammed Kürşat (My University, 2025)
Global literacy refers to the ability to recognize the political, ecological, and economic aspects of developments worldwide, access global information, classify and use information, and understand and interpret the power and effectiveness of information technologies and mass media. The aim of this study was to examine the global literacy levels of pre-service teachers and the factors affecting these levels. A cross-sectional survey design, one of the quantitative research methods, was used in the study. The sample consisted of 701 pre-service teachers studying in various teacher education programs at the faculty of education of a public university, selected through convenience sampling, and who voluntarily participated in the study. The data were collected using the Global Literacy Scale (GLS), developed by the researchers, and analyzed using the SPSS Statistics program. Descriptive statistics, independent samples t-test, and one-way analysis of variance (ANOVA) were used in the data analysis. The findings revealed that pre-service teachers had high levels of global literacy, global awareness, and global attitudes, while their level of global participation was moderate. In addition, significant differences were found in the overall scale and its sub-dimensions based on gender, grade level, department, and foreign language proficiency. Based on the results of the study, it is recommended that practical activities be organized—especially to enhance the level of global participation—and that global literacy be integrated into undergraduate programs.
Keywords: Pre-service Teachers; Global Literacy; Global Awareness; Global Attitude; Global Participation